Qualitative Clinical Trial Exit Interviews Evaluating Treatment Benefit, Burden, and Satisfaction in Patients with Schizophrenia. (April 2021) - Simmons, Adam; Carpenter-Conlin, Julia; Bessonova, Leona; O'Sullivan, Amy K.; McDonnell, David; Saucier, Cory; White, Michelle K.; Foster, April M.; Bjorner, Jakob B.; Lapeyra, Olga; Walling, David P.
Abstract: Objective: An open-label extension study (NCT02873208) evaluated the long-term tolerability, safety, and efficacy of combination olanzapine/samidorphan (OLZ/SAM) treatment in patients with schizophrenia. This qualitative sub study explored perceptions of benefit, burden, and satisfaction with previous medications and OLZ/SAM. Methods: Semi-structured interviews (60 minutes; audio-recorded) were conducted. Interviewer sensitivity training, senior interviewer oversight, and a list of common medications to aid recall supported data collection. Interview transcripts were content coded and analyzed (NVivo v11.0). Results: All 41 patients reported a lifetime burden with schizophrenia adversely impacting employment, relationships, emotional health, social activities, and daily tasks. Hospitalization for schizophrenia management was another reported aspect of disease burden. Although most (n=32) patients reported previous medication benefits, side effects affecting physical, emotional/behavioral, and cognitive functioning were reported by all (n=41). Following OLZ/SAM treatment, 39/41 patients (95%) reported improvements in symptoms including hallucinations, paranoia, depression, sleep, and concentration. Furthermore, patients described improvements in self-esteem, social activities, relationships, and daily activities. Twenty-three patients (56%) reported side effects attributed to OLZ/SAM; lack of energy (n=12 [29%]) and dry mouth (n= 5 [12%]) were most common. Twenty-four (59%) patients were "very satisfied" with OLZ/SAM; most (n=35 [85%]) preferred to continue OLZ/SAM vs switching to another medication. As most substudy patients (n=40; 98%) completed the extension study, satisfied patients may be overrepresented in this analysis. Conclusion: This qualitative interview approach provided valuable insight into patients' experiences with previous medications and OLZ/SAM. Overall, most patients reported treatment satisfaction and improvements in symptoms, function, and health-related quality of life with OLZ/SAM. Funding: Alkermes, Inc.